Chemical space as a unifying theme for chemistry - Jean-Louis Reymond (Journal of Cheminformatics)
Abstract Chemistry has diversified from a basic understanding of the elements to studying millions of highly diverse molecules and materials, which together are conceptualized as the chemical space. A map of this chemical space where distances represent similarities between compounds can represent the mutual relationships between different subfields of chemistry and help the discipline to be viewed and understood globally.